Molecular Characteristics of Dissolved Organic Nitrogen in PM2.5 from Shanghai by FT-ICR Mass Spectrometry - Ning Cuiping; Tang Yutong; Wang Dan (E3S Web of Conferences)
Dissolved organic nitrogen (DON) is a significant contributor to atmospheric organic nitrogen, and it can influence the global nitrogen cycle. However, its composition and sources remain largely unknown. We collected atmospheric fine particulate matter (PM2.5) in Shanghai and analyzed the molecular compositions of DON using Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). The results showed that 902 dissolved organic nitrogen molecular formulas were identified in PM2.5 during the summer in Shanghai. The molecular weight of DON ranged from 200 to 600 Da. The DON compounds included CHON1 and CHON2, with CHON2 having a higher O/C ratio. The DON was mainly composed of lipid-like compounds, aliphatic/peptide-like compounds, and carbohydrate-like compounds, with their contributions being 37.3%, 35.9%, and 11.2%, respectively. A total of 95% of the CHON compounds had an O/N≥3, indicating that these compounds carried the -ONO2 functional group and might be organonitrate compounds. Source apportionment analysis revealed that dissolved organic nitrogen mainly comprised semi-volatile oxidized organic aerosol, low volatile oxidized organic aerosol , and biomass burning organic aerosol.